Catalytic Radical Process for Enantioselective Amination of C(sp3)−H Bonds. (16th November 2018) - Li, Chaoqun; Lang, Kai; Lu, Hongjian; Hu, Yang; Cui, Xin; Wojtas, Lukasz; Zhang, X. Peter
Abstract: A new catalytic radical system involving Co II ‐based metalloradical catalysis is effective in activating sulfamoyl azides for enantioselective radical 1, 6‐amination of C(sp 3 )−H bonds, affording six‐membered chiral heterocyclic sulfamides in high yields with excellent enantioselectivities. The Co II ‐catalyzed C−H amination features an unusual degree of functional‐group tolerance and chemoselectivity. The unique reactivity and stereoselectivity is attributed to the underlying stepwise radical pathway. The resulting optically active cyclic sulfamides can be readily converted into synthetically useful chiral 1, 3‐diamine derivatives without loss in enantiopurity. Abstract : Radikale und Co .: Eine Cobalt(II)‐basierte Metalloradikalkatalyse (MRC) ermöglicht die stereoselektive Aminierung aliphatischer C‐H‐Bindungen bei Raumtemperatur zur Bildung chiraler 1, 3‐Diamine unter neutralen nichtoxidierenden Bedingungen. Die Cobalt(II)‐katalysierte C‐H‐Aminierung ist außergewöhnlich chemoselektiv und verträglich mit funktionellen Gruppen.